Hospital Variation in Textbook Outcomes Following Curative-Intent Resection of Hepatocellular Carcinoma: an International Multi-Institutional Analysis - Tsilimigras, D (2020)
Background: Composite measures such as "Textbook Outcome" (TO) may be superior to individual quality metrics to assess surgical care and hospital performance. However, the incidence and factors associated with TO after resection of HCC remain poorly defined. Methods: Hospital variation in the rates of TO, factors associated with achieving a TO and the impact of TO on long-term survival following resection for HCC were examined using an international multi-institutional database. Results: Among 605 patients who underwent curative-intent resection of HCC, the unadjusted incidence of TO ranged from 50.9% to 77.7%. While achievement of each individual quality metric was relatively high (range, 74.5-98.0%), an overall TO was achieved among only 62.3% (n = 377) of patients. At the hospital level, TO ranged from 54.3% to 72.9%. Patients with BCLC-0 HCC (referent BCLC-B/C; OR: 4.17, 95%CI: 1.62-10.7) and ALBI grade 1 (referent ALBI grade 2/3; OR: 1.49, 95%CI: 1.06-2.11) had higher odds of achieving a TO. On multivariable analysis, TO was associated with improved overall survival (HR: 0.60, 95% CI: 0.42-0.85). Conclusion: Roughly 6 in 10 patients achieved a TO following resection for HCC. When achieved, TO was associated with better long-term outcomes. TO is a simple composite measure of both short- and long-term outcomes among patients undergoing resection for HCC.